A Global Approach to Digital Library Evaluation - Vullo, Giuseppina (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
This paper describes the key advances on digital library evaluation research. The paper provides a comparison of the existing models, the current research questions in this area, an integrated LIS-oriented evaluation framework, and a selection of international projects.